Challenges of Data Analytics for Innovative V’s and Security in Bigdata - Angelin Rosy, M; Deepa, R; Felix Xavier Muthu, M (International Journal of Computer Sciences and Engineering, 2025)
Data sets that may be analyzed computationally behavior, interactions are too large. Big data considering the security point of view is safeguarding the user’s privacy. A framework for big data security analysis and the semantic technology. The emerging security analysis challenge in big data environment is getting more attention of security. Framework that efficiently processes large volumes of data. The big data analytics is merged with big data security which results in big data security analytics. In this paper, I explain the big data challenges and privacy of outsourced enhancing security be handled by analytics techniques. Big data main problem is privacy of security challenges.